2014
DOI: 10.1007/s13277-014-1965-2
|View full text |Cite
|
Sign up to set email alerts
|

miR-22 inhibits osteosarcoma cell proliferation and migration by targeting HMGB1 and inhibiting HMGB1-mediated autophagy

Abstract: Acquisition of drug-resistant phenotypes is often associated with chemotherapy in osteosarcoma. Studies show that high-mobility group box 1 (HMGB1) plays an important role in facilitating autophagy and promotes drug resistance in osteosarcoma cells. In this study, we determined the targeting role of miR-22 to HMGB1 and the regulation of miR-22 on the HMGB1-mediated cell autophagy and on the cell proliferation, migration, and invasion of osteosarcoma cells. Results demonstrated that miR-22 well paired with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(53 citation statements)
references
References 39 publications
5
48
0
Order By: Relevance
“…Because of the advancement of its treatment, including surgery and multi‐agent chemotherapy, the 5‐year survival rate in patients with primary osteosarcoma has improved over the past several decades 5, 6, 7, 8. However, the survival rate for this tumour remains low 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Because of the advancement of its treatment, including surgery and multi‐agent chemotherapy, the 5‐year survival rate in patients with primary osteosarcoma has improved over the past several decades 5, 6, 7, 8. However, the survival rate for this tumour remains low 9, 10, 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated that HMGB1 is an important regulator of autophagy and that HMGB1-regulated autophagy is a significant contributor to drug resistance following treatment with cytotoxic agents in tumor cells32344748. In the present study, we found that OMT increased the expression of HMGB1 in a dose- and time-dependent manner.…”
Section: Discussionsupporting
confidence: 70%
“…However, possibly as a compensatory effect, miR-22 was also upregulated during chemotherapy; and overexpressed miR-22 targeted the 3′UTR of HMGB1 and inhibited HMGB1-promoted autophagy [102]. Additionally, miR-22 inhibited osteosarcoma cell proliferation and migration by targeting HMGB1 and inhibiting HMGB1-mediated autophagy [103]. The upregulated HMGB1 increased the formation of the Beclin1-PtdIns3KC3 complex and stimulated autophagosome maturation and autophagy by competing with Bcl-2 to bind Beclin1.…”
Section: Programmed Cell Death In the Treatment Of Osteosarcomamentioning
confidence: 99%